Youth Civic Engagement in the Era of Social Media Activism - Omodolapo Eunice Ogunsola (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
The rise of social media has significantly transformed the landscape of youth civic engagement, offering new avenues for political participation, activism, and public discourse. This review explores how digital platforms such as Twitter, Instagram, TikTok, and Facebook have reshaped traditional models of youth activism by enabling real-time mobilization, grassroots campaigns, and transnational solidarity movements. It critically examines the dual role of social media in empowering youth voices while also presenting challenges related to misinformation, algorithmic bias, and performative activism. Drawing from multidisciplinary literature, the paper analyzes the evolving definitions of civic engagement in the digital age, the mechanisms through which youth navigate and influence sociopolitical spaces online, and the implications for democratic participation. Case studies from recent global movements—such as #FridaysForFuture and #EndSARS—demonstrate how digital activism fosters political efficacy, identity formation, and issue-based alliances. Ultimately, this review provides a nuanced understanding of the opportunities and limitations of social media-driven civic engagement, offering recommendations for enhancing the digital civic capacity of young people in a rapidly changing media environment.